Synthesis of α-Branched Acyclic Nucleoside Phosphonates as Potential Inhibitors of Bacterial Adenylate Cyclases - Frydrych, Jan; Skácel, Jan; Šmídková, Markéta; Mertlíková-Kaiserová, Helena; Dračínský, Martin; Gnanasekaran, Ramachandran; Lepšík, Martin; Soto-Velasquez, Monica; Watts, Val J; Janeba, Zlatko (ChemMedChem, 2018)
Inhibition of Bordetella pertussis adenylate cyclase toxin (ACT) and Bacillus anthracis edema factor (EF), key virulence factors with adenylate cyclase activity, represents a potential method for treating or preventing toxemia related to whooping cough and anthrax, respectively. Novel α-branched acyclic nucleoside phosphonates (ANPs) having a hemiaminal ether moiety were synthesized as potential inhibitors of bacterial adenylate cyclases. ANPs prepared as bisamidates were not cytotoxic, but did not exhibit any profound activity (IC50 >10 μm) toward ACT in J774A.1 macrophages. The apparent lack of activity of the bisamidates is speculated to be due to the inefficient formation of the biologically active species (ANPpp) in the cells. Conversely, two 5-haloanthraniloyl-substituted ANPs in the form of diphosphates were shown to be potent ACT and EF inhibitors with IC50 values ranging from 55 to 362 nm.
Keywords: Cell Line; Adenylyl Cyclase Inhibitors; adenylate cyclase toxin; simulace molekulového dockingu; Protein Binding; inhibitory adenylylcyklasy; prodrugs; antigeny bakteriální; Molecular Docking Simulation; Organophosphonates; Antigens, Bacterial; Bacterial Proteins; bisamidates; Bacterial Toxins; Macrophages; Bordetella pertussis; Nucleosides; Protein Conformation; bakteriální toxiny; Humans; nukleosidy; vazba proteinů; viabilita buněk; Cell Survival; makrofágy; adenylátcyklasový toxin; Adenylate Cyclase Toxin; buněčné linie; bakteriální proteiny; organofosfonáty; acyclic nucleoside phosphonates; lidé; konformace proteinů